Geosynthetics for sustainable cities: 3D numerical models and mechanical damage - Paiva, Lucas (2022)
Geotechnical works play a major role on the infrastructure development. Geosynthetics are the most efficient, cost-effective and environmentally- friendly solution to a variety of geotechnical structures (e.g., roadways, foundations, retaining walls). Thus, improving the design methods of geosynthetics can increase safety and reduce infrastructure costs (GDS goal 9).